Ambidextrous strategy antecedents, strategic choices, and performance - Zakrzewska-Bielawska, Agnieszka, 1973- (London : Routledge, 2021)
Strategies of enterprises evolve with the development of strategic management theory and new concepts, models, and outlooks that emerge with it. The concept of ambidexterity is a relatively new approach to business development strategies, which involves simultaneous exploration and exploitation activities to ensure the success of the company and a relatively sustainable competitive advantage. This begs the question as to whether the ambidextrous strategy is the right choice for all enterprises, and if not, what determines its choice. This book identifies and systematizes antecedents for choosing ambidextrous strategy, including factors related to the uncertainty of the environment, its dynamics, complexity, and unpredictability, intra-organizational factors, those related to resources, organizational structure, and behavioral context, as well as those related to strategic leadership. It examines the outcomes of implementing ambidexterity from the perspective of financial and market performance and assesses the choices of companies operating in Poland from the perspective of the impact that particular antecedents had and the outcomes achieved, providing knowledge and guidance on the circumstances in which choosing the ambidextrous strategy brings the best results. The book presents the research findings to date, the cognitive gaps that still exist, and the directions for further research. It is intended for scientific circles, doctoral and management students and a wide range of managers, who have to make difficult strategic choices aimed, on the one hand, at increasing the efficiency of the company and, on the other, at seeking new paths of growth.
OCLC-licensed vendor bibliographic record.
Keywords: Strategic planning; Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership